Second Renal Transplantation With Simultaneous Ileal Conduit Creation Following Transplant Nephroureterectomy and Native Cystectomy - Ayato Ito; Takehiro Ohyama; Kyoko Minamisono; Sho Nishida; Daiki Iwami (IJU Case Reports)
ABSTRACT Introduction Postrenal transplant urothelial carcinoma necessitates multidisciplinary treatment. We here report the first case of a patient with transplant ureteral and bladder cancer who underwent transplant nephroureterectomy and cystectomy, followed by a second living donor renal transplantation and ileal conduit creation after a cancer recurrence‐free period. Case Presentation A 78‐year‐old female with end‐stage renal disease who had previously undergone living donor renal transplantation presented with gross hematuria. She was diagnosed with transplant ureteral and bladder cancer and subsequently underwent transplant nephroureterectomy and cystectomy. She was immediately reintroduced to hemodialysis. After a 2‐year cancer‐free period, a second living donor renal transplantation with simultaneous ileal conduit surgery was successfully performed. Currently, the patient remains cancer‐free for 2 years following the second renal transplantation. Conclusion Second renal transplantation and simultaneous ileal conduit creation are alternatives following curative transplant nephrouretero‐cystectomy for post‐transplant urothelial carcinoma.